2022
DOI: 10.3390/antiox11101895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma-Tocotrienol on Partial-Body Irradiation-Induced Intestinal Injury in a Nonhuman Primate Model

Abstract: Exposure to high doses of radiation, accidental or therapeutic, often results in gastrointestinal (GI) injury. To date, there are no therapies available to mitigate GI injury after radiation exposure. Gamma-tocotrienol (GT3) is a promising radioprotector under investigation in nonhuman primates (NHP). We have shown that GT3 has radioprotective function in intestinal epithelial and crypt cells in NHPs exposed to 12 Gy total-body irradiation (TBI). Here, we determined GT3 potential in accelerating the GI recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…To evaluate PD-L1, CD8, and MHC-1 expression in formalin-fixed paraffin-embedded tissue sections of mouse tumors, immunohistochemical staining was performed with conventional techniques using an avidin-biotin complex, diaminobenzidine chromogen, and hematoxylin counterstaining (26). Sections (4 µm thick) were deparaffinized, rehydrated and blocked for endogenous peroxidase, followed by incubation with rabbit anti-PD-L1 (64988, 1:100, Cell Signaling Technology), rat anti-CD8 (14-0808-80, 1:50, Invitrogen, Waltham, MA) and rabbit anti-MHC-1 (NBP3-09017, 1:50, Novus Biologicals, Centennial, CO) overnight at 4ºC.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To evaluate PD-L1, CD8, and MHC-1 expression in formalin-fixed paraffin-embedded tissue sections of mouse tumors, immunohistochemical staining was performed with conventional techniques using an avidin-biotin complex, diaminobenzidine chromogen, and hematoxylin counterstaining (26). Sections (4 µm thick) were deparaffinized, rehydrated and blocked for endogenous peroxidase, followed by incubation with rabbit anti-PD-L1 (64988, 1:100, Cell Signaling Technology), rat anti-CD8 (14-0808-80, 1:50, Invitrogen, Waltham, MA) and rabbit anti-MHC-1 (NBP3-09017, 1:50, Novus Biologicals, Centennial, CO) overnight at 4ºC.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For example, several studies have shown that γ-tocotrienol (γGT3), a saturated vitamer of vitamin E, exerts protective effects on hematopoietic stem cells and intestinal crypt cells in the gastrointestinal tract in murine and nonhuman primate (NHP) models, accelerating recovery from IR-induced injury at various doses (5.8, 6.5, 11, or 12 Gy). [24][25][26][27][28][29][30][31] The radioprotector, indralin (B-190), was also shown to exhibit radioprotective effects on hematopoietic and other tissues, including the intestines, skin, testes, and salivary glands, and it improved survival rates in monkeys after total-body irradiation (TBI) at a dose of 6.8 Gy. [32][33][34][35][36] BIO300, a suspension of synthetic genistein nanoparticles, was developed by the Humanetics Corporation to prevent and mitigate the effects of ARS and DEARE, and radioprotective effects have been demonstrated in mice and NHPs.…”
Section: The Mechanism Of Ir-induced Injurymentioning
confidence: 99%
“…Some antioxidants are being investigated as radioprotective agents for ARS. For example, several studies have shown that γ‐tocotrienol (γGT3), a saturated vitamer of vitamin E, exerts protective effects on hematopoietic stem cells and intestinal crypt cells in the gastrointestinal tract in murine and nonhuman primate (NHP) models, accelerating recovery from IR‐induced injury at various doses (5.8, 6.5, 11, or 12 Gy) 24–31 . The radioprotector, indralin (B‐190), was also shown to exhibit radioprotective effects on hematopoietic and other tissues, including the intestines, skin, testes, and salivary glands, and it improved survival rates in monkeys after total‐body irradiation (TBI) at a dose of 6.8 Gy 32–36 .…”
Section: Advancement In the Development Of Radioprotective Agentsmentioning
confidence: 99%
“…In addition to HSCs and HPCs, GT3 reduced radiation-induced persistent DNA damage of lymphoid/myeloid progenitor cells, while significantly inducing G-CSF (granulocyte-colony stimulating factor), a crucial factor in stem cell mobilization and hematopoietic recovery (36,37). Interestingly, GT3 also demonstrated its radioprotective role in intestinal epithelial and crypt cells in an NHP model exposed to a supralethal dose of radiation (38,39). Most importantly, GT3 is under advanced development as a radioprotective MCM following the U.S. FDA Animal Rule to be used as a pre-exposure prophylaxis for H-ARS (31).…”
Section: Introductionmentioning
confidence: 99%